2011
DOI: 10.1007/s11846-011-0068-3
|View full text |Cite
|
Sign up to set email alerts
|

Intensity, timeliness, and success of incumbent response to technological discontinuities: a synthesis and empirical investigation

Abstract: The extant literature highlights numerous different factors influencing the timeliness and intensity of incumbent response to discontinuous technological change. However, this literature has so far not been synthesized and is therefore limited in its analytical, predictive, and normative power. We develop a comprehensive model of incumbent response that organizes different explanatory factors into the three distinct dimensions of (1) identification and interpretation, (2) decision making, and (3) organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…Individuals with high EO evaluate uncertainty more as an opportunity than a threat (Palich and Ray Bagby 1995;Weaver et al 2002). This kind of opportunity framing implies more intense and faster reactions (Bockmühl et al 2011) with the risk of working at high speed in the wrong directions and damaging product innovation.…”
Section: Technological Uncertainty and Eomentioning
confidence: 99%
“…Individuals with high EO evaluate uncertainty more as an opportunity than a threat (Palich and Ray Bagby 1995;Weaver et al 2002). This kind of opportunity framing implies more intense and faster reactions (Bockmühl et al 2011) with the risk of working at high speed in the wrong directions and damaging product innovation.…”
Section: Technological Uncertainty and Eomentioning
confidence: 99%
“…Some others have adopted a different approach and decided to empirically test the impact of these frameworks and of their success factors (e.g. Pinto and Prescott, 1990;Miller, 1997;Bauer et al, 2005;Bockmühl et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Firms with a high degree of market sensitivity continuously scan existing and potential markets, thus maintaining an ability to develop a timely response to discontinuous change (Bockmühl et al, 2011). A failure to detect changes in the political environment and engage with the firm's institutional context may lead to the demise of even the biggest corporations (Dixon and Day, 2010).…”
Section: Understand the Environmentmentioning
confidence: 99%
“…Technicians were now able to scan and produce customised prostheses through a highly automated process, instead of relying on traditional manual techniques. An empirical study of this industry's responses to the changes (Bockmühl et al, 2011) found that the firms that systematically searched and collected market information, intensively discussed and evaluated the impact and searched for new markets were able to adjust faster than the companies less conscious of changes outside of their traditional industry and core competences.…”
Section: Understand the Environmentmentioning
confidence: 99%
See 1 more Smart Citation